(untitled) (Journal of Information Technologies in Education (ITE), 2020)
The article is devoted to the problem of clarifying the possibilities of using specialized applied software for modeling electronic devices based on the Arduino platform during non-formal education of children. The article analyzes the current state of the issue of STEM-education in general secondary education. The authors of the article carried out a thorough analysis of the Arduino open-source software complex. The history of Arduino creation and the most widespread platforms of its model line are described, examples of application of the specified platforms in real-life projects are given. The main technical specs and characteristics of the Arduino Uno electronic elements are presented and analyzed. Atmega328P microcontroller is reviewed, including the main calculative center of the platform and its major hardware components. Specialized applied software for creating visual electronic circuits “Fritzing” is described, its benefits are considered. This software product provides the opportunity to visually present the project (creation of a digital model) in different types (layout, scheme and printed circuit board). Any of the above mentioned emanations of the model can be used as the main work environment of the project and can be selected at any time. For better clarity and usability all the processes of creating a prototype of the electronic game "Hunter" in the specialized applied software “Fritzing” are described and illustrated, including the description of game development process. The results of the research indicated the importance of developing modern approaches to non-formal education of children and the need for systematic review of training programs for computer science (CS) teachers